Effect of Biostimulants on Drought Tolerance of Greenhouse-Grown Tomato - Kalliopi I. Kadoglidou; Eleni Anthimidou; Konstantinos Krommydas; Eleni Papa; Eleftherios Karapatzak; Nektaria Tsivelika; Maria Irakli; Ifigeneia Mellidou; Aliki Xanthopoulou; Apostolos Kalivas (Horticulturae)
The use of biostimulants is one of the recognized strategies for mitigating the adverse effects of drought on crops. In a greenhouse tomato experiment, the effect of two biostimulants in combination with three levels of drought was investigated. Specifically, the doses of 150 mL and 1000 g ha−1 of a plant-derived polyhydroxy acids extract (B1) and a Sargassum seaweed extract (B2), respectively, were studied in combination with drought levels of 85, 63.75, and 42.5% of field capacity. Four applications were performed during key growth stages. The effects were comprehensively investigated by assessing agronomic and physiological traits of the plants at three defined time points during the experimental period. Furthermore, organoleptic characteristics, bioactive compounds, antioxidant activity in the fruits, and overall yield components were evaluated. Drought stress provoked a consistent negative impact on several physiological traits, such as stomatal conductance (up to −58.3%), net photosynthesis (up to −47.9%), and quantum yield. A comparable impact was observed on agronomic traits, such as plant height, stem thickness, and number of leaves, with reductions of up to 13.6%. Both biostimulants’ applications enhanced certain physiological features across all irrigation levels, including net photosynthesis by up to 44.3% and chlorophyll content index by up to 33.4%, while B2 further increased intrinsic water use efficiency by up to 42.9% compared to the respective controls. However, this trend was not reflected in the evaluated post-harvest parameters, such as fruit yield, fruit number, fruit weight, and quality indices. These findings suggest that biostimulants may have a supporting role in physiological responses under drought stress but have limited effects on fruit production. Future research should focus on optimizing the formulation, dosage, and timing of biostimulant applications, as these factors may be critical to enhancing plant tolerance to drought stress and improving fruit yield responses.